Encyclopedia of otolaryngology, head and neck surgery - Kountakis, Stilianos E. (Springer Berlin Heidelberg, 2013)
The encyclopedia of otolaryngology-head and neck surgery will be a comprehensive collection of works that will serve as a complete source of information for all otolaryngologists, including the ones in training and interested medical students or health care personnel. This reference work will be multivolume, divided into 5 distinct sections, each section approximately 1000 pages long. Each volume will contain clearly defined and structured entries in an A-Z format, providing the reader with quick and easy access to the required information. The online version will be fully searchable and will turn this reference work into an invaluable information tool for experts and newcomers in the field.